PENGARUH PENGGUNAAN MEDIA GAMBAR TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS VA SDN DUKUH MENANGGAL I/424 SURABAYA - Khoirunnisa, Labibah Putri Likmanda; Sumiharsono, Rudy; Danang Prastyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study uses a causal quantitative method with a posttest-only research design. This study has a problem formulation of Is There an Effect of Using Picture Media on the Learning Outcomes of Indonesian Language of Class VA Students of SDN Dukuh Menanggal I/424 Surabaya. This study aims to determine Is There an Effect of Using Picture Media on the Learning Outcomes of Indonesian Language of Class VA Students of SDN Dukuh Menanggal I/424 Surabaya. This study used a population of all class V students of SDN Dukuh Menanggal I/424 Surabaya totaling 61 students. The sample used was 30 class VA students as the main respondents and 31 class VB students as supporting respondents used in the study. This study has 2 variables, namely variable X picture media and variable Y learning outcomes. This study was motivated by the problem of the learning outcomes of class VA students of SDN Dukuh Menanggal I/424 Surabaya which are still relatively low. Some students are not enthusiastic about learning because of the lack of supporting facilities (learning media). Data collection techniques used questionnaires, tests, interviews, and documentation. Instrument testing used validity and reliability. Prerequisite testing used normality tests and homogeneity tests. Hypothesis test in the form of t-test. To find out the value of the t-table distribution, it is seen based on df = 28 with a level of a = 0.05. Because the calculated t value> t table (25,362> 1.70113) and sig (2-tailed) 0.01 <0.05, then H0 is rejected. This means that the hypothesis states a significant influence on the Use of Image Media on the Learning Outcomes of Indonesian Language of Class VA Students of SDN Dukuh Menanggal I/424 Surabaya.